Method for producing tempered glass, and ion exchange liquid

By adding boron compound as a pH adjuster to the ion exchange liquid, the problem of the surface strength of the reinforced glass due to the rise in the pH of the ion exchange liquid is solved, and the manufacturing of reinforced glass with high surface strength and low surface defects is achieved.

CN119768377APending Publication Date: 2025-04-04NIPPON ELECTRIC GLASS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064305.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-08-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When existing ion exchange liquids are used for a long time at high temperatures, the pH is prone to rise, resulting in a decrease in the surface strength and transparency of the reinforced glass, and the problem of poor white and turbid appearance.

Method used

The addition of boron compound as a pH adjuster to the ion exchange liquid ensures that even if the pH rises, the pH of the ion exchange liquid can be effectively reduced by the boron compound, thereby inhibiting the reduction of the surface strength of the reinforced glass.

Benefits of technology

By adjusting the pH of the ion exchange liquid with boron compounds, it is possible to effectively suppress the reduction of the surface strength of the reinforced glass, reduce the surface defect, and maintain the high transparency of the reinforced glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768377A_ABST
    Figure CN119768377A_ABST
Patent Text Reader

Abstract

A method for producing tempered glass, said method being provided with a step in which an ion exchange liquid (2) is brought into contact with a glass (1) for strengthening, which contains an alkali metal component, and the glass (1) for strengthening is subjected to an ion exchange treatment. The ion exchange liquid (2) contains a molten salt (2a) and a boron compound (2b) as a pH regulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing tempered glass and an ion exchange liquid. Background Art

[0002] In recent years, tempered glass has been widely used in cover glasses of various electronic terminals, display devices, etc. Tempered glass has a compressive stress layer formed by ion exchange treatment on the surface layer, and has high surface strength that can inhibit the formation and development of surface cracks.

[0003] In the ion exchange treatment, the tempered glass is immersed in an ion exchange solution containing a molten salt, so that the alkali ions with a small ion radius in the tempered glass are exchanged with the alkali ions with a large ion radius in the molten salt, thereby forming a compressive stress layer on the surface of the tempered glass. In this case, as the molten salt, for example, NaNO 3 of molten salt.

[0004] In addition, in the ion exchange treatment, there is also the case where the compressive stress of the compressive stress layer formed on the surface of the strengthened glass can be relieved by immersing the strengthened glass in an ion exchange liquid containing a molten salt, and performing reverse ion exchange between the alkali ions with a large ion radius in the strengthened glass and the alkali ions with a small ion radius in the molten salt (for example, refer to Patent Document 1). This reverse ion exchange is performed separately from the above-mentioned ion exchange, or simultaneously with the above-mentioned ion exchange. In this case, as the molten salt, for example, a molten salt containing LiNO 3 of molten salt.

[0005] From the viewpoint of mass productivity, it is customary to repeatedly use such an ion exchange solution for a plurality of tempering glasses. However, if the ion exchange solution is used for a long time at a high temperature, it may deteriorate with an increase in pH.

[0006] Patent Document 2 states that if an ion exchange treatment is performed using such a degraded ion exchange liquid, the OH in the ion exchange liquid - The precipitates caused by the precipitates cause a white turbid appearance defect that reduces the transparency of the tempered glass. In order to suppress the occurrence of such a white turbid appearance defect, the same document adds silicate to an ion exchange liquid containing a molten salt to reduce the pH of the ion exchange liquid.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2020 / 075709

[0010] Patent Document 2: Japanese Patent Application Publication No. 2021-59481 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The silicic acid described in Patent Document 2 has low solubility in water. Therefore, if the silicic acid added to the ion exchange liquid adheres to the surface of the tempered glass, it is difficult to remove it by washing. As a result, the tempered glass may suffer from surface defects caused by the silicic acid.

[0013] In addition, the inventors of the present application have found through intensive research that if an ion exchange treatment is performed using an ion exchange liquid that deteriorates as the pH increases, the surface strength of the tempered glass may decrease even if white turbidity and poor appearance do not occur. This is believed to be due to the fact that OH in the ion exchange liquid - The surface of the tempered glass is partially corroded and becomes rough. Therefore, regardless of whether white turbidity or poor appearance occurs, it is necessary to reliably suppress the increase in pH of the ion exchange liquid.

[0014] The present invention aims to reliably suppress the increase in pH of an ion exchange solution and to produce a tempered glass having few surface defects and high surface strength.

[0015] Means of solving the problem

[0016] (1) The present invention made to solve the above-mentioned problems is a method for producing tempered glass, characterized by comprising a step of bringing an ion exchange liquid into contact with tempered glass containing an alkali metal component to thereby subject the tempered glass to an ion exchange treatment, wherein the ion exchange liquid contains a molten salt and a pH adjuster, and the pH adjuster is a boron compound.

[0017] If so, even if the pH of the ion exchange liquid rises, the pH of the ion exchange liquid can be reliably lowered by using a pH adjuster composed of a boron compound. Thus, it is possible to suppress the reduction in the surface strength of the manufactured tempered glass. In addition, if the pH adjuster is a boron compound, it has high solubility in water, so even if the pH adjuster adheres to the tempered glass, it can be easily removed by washing. In other words, it is difficult for the tempered glass to have surface defects caused by the pH adjuster.

[0018] (2) According to the configuration of (1) above, the pH adjuster preferably contains B 2 O 3 and B(OH) 3 as a boron compound.

[0019] In this way, the pH adjuster is stable in the ion exchange liquid, so that an unnecessary reaction is unlikely to occur. In addition, the pH adjuster has good solubility in water.

[0020] (3) The configuration according to (1) or (2) above, wherein the content of the pH adjuster in the ion exchange liquid is preferably 0.1 to 10 parts by mass based on 100 parts by mass of the molten salt.

[0021] When the pH adjuster is a boron compound, the pH of the ion exchange liquid can be reliably lowered even with such a small content.

[0022] (4) The configuration according to any one of (1) to (3) above, wherein the pH of the ion exchange liquid when mixed with water to form an aqueous solution having a concentration of 20% by mass is preferably 8 or less.

[0023] With this configuration, it is possible to more reliably suppress a decrease in the surface strength of the tempered glass.

[0024] (5) The configuration according to any one of (1) to (4) above, wherein the content of the pH adjuster in the ion exchange solution is preferably adjusted so that the surface roughness Sa of the tempered glass is 3.0 nm or less.

[0025] With this configuration, it is possible to more reliably suppress a decrease in the surface strength of the tempered glass.

[0026] (6) The configuration according to any one of (1) to (5) above, wherein the pH adjuster is preferably contained in the ion exchange liquid in the form of a powder or an aggregate of powder.

[0027] In this case, the treatment with the pH adjuster can be easily performed.

[0028] (7) According to the configuration of (6), the ion exchange treatment is preferably performed by placing the ion exchange liquid and the strengthening glass in an ion exchange tank, and the pH adjuster is placed in the ion exchange tank in a state separated from the strengthening glass by a separation member through which the ion exchange liquid can pass.

[0029] With this configuration, it is possible to prevent unreacted pH adjuster from being attached to the strengthening glass (or strengthened glass) and being carried out of the ion exchange tank.

[0030] (8) According to the configuration of (7) above, the pH adjuster is preferably arranged in a bottom layer portion of the ion exchange tank using a partition member.

[0031] The boron compound as a pH adjuster has a low density and floats in the ion exchange liquid, but if a separation member is used, it can be sunk to the bottom of the ion exchange tank. As a result, it is easy to maintain the state in which the boron compound is separated from the tempering glass. In addition, a part of the boron compound that passes through the separation member is dispersed in the ion exchange liquid during the process of rising in the ion exchange liquid by buoyancy. Therefore, the pH of the entire ion exchange liquid can be effectively lowered.

[0032] (9) The configuration according to any one of (1) to (8) above, wherein the molten salt preferably contains LiNO 3 and NaNO 3 At least one of .

[0033] Contains LiNO 3 and NaNO 3 At least one of the molten salts is likely to undergo a decomposition reaction, and the pH rise of the ion exchange solution caused by the decomposition reaction is likely to occur. In particular, LiNO 3 The temperature at which the decomposition reaction occurs is low, so the pH is likely to rise. Therefore, it is particularly useful to use a pH adjuster composed of a boron chemical for such a molten salt.

[0034] (10) According to the configuration of (9) above, it is preferred that the molten salt does not substantially contain KNO 3 .

[0035] Contains KNO 3 The decomposition reaction of the molten salt is difficult to occur, and the pH increase of the ion exchange liquid caused by the decomposition reaction is difficult to occur. 3 and NaNO 3 At least one of the following, and substantially no KNO 3 For molten salts, it is particularly useful to use a pH adjuster composed of a boron compound.

[0036] (11) The configuration according to (9) or (10) above, preferably, further comprising a step of performing a two-stage ion exchange treatment, wherein the ion exchange solution is used in the first-stage ion exchange treatment.

[0037] In this way, it is possible to suppress the increase in pH of the first-stage ion exchange solution, form a deep compressive stress layer in the first-stage ion exchange treatment, and impart high surface compressive stress to the tempered glass in the second-stage ion exchange treatment.

[0038] (12) According to any one of (1) to (11) above, the tempered glass preferably contains 1 mol % or more of Li 2 O of alkali aluminosilicate glass.

[0039] If so, by performing a two-stage ion exchange treatment, etc., it is easy to achieve a high surface compressive stress, and at the same time, the compressive stress layer is formed deeply. On the other hand, during the ion exchange treatment, Li ions are dissolved from the tempering glass, and the Li ion concentration in the ion exchange liquid increases. If the Li ion concentration rises like this, it may hinder the progress of the ion exchange treatment. If it is a pH adjusting agent composed of a boron compound, it can also adsorb the Li ions in the ion exchange liquid during the reaction process that lowers the pH of the ion exchange liquid. Therefore, it has the following effect, even if a lithium adsorption material that adsorbs Li ions other than the pH adjusting agent is not added, the Li ion concentration in the ion exchange liquid can be reduced, and the progress of ion exchange can be well maintained.

[0040] (13) According to the configuration of (12) above, it is preferred that the tempering glass contains SiO as a glass composition in terms of mol%. 2 40~80%,Al 2 O 3 1~30%, B 2 O 3 0~10%,MgO 0~10%,Li 2 O 1~28%, Na 2 O 1~25%, K 2 O 0~10%, P 2 O 5 0~10%, ZrO 2 0~10%.

[0041] (14) The configuration according to any one of (1) to (13) above, preferably further comprising the step of measuring the pH of the ion exchange liquid and the step of adding a pH adjuster to the ion exchange liquid based on the pH measurement result.

[0042] In this way, after confirming that the pH of the ion exchange liquid has increased, a pH adjuster can be added. In other words, it is easy to always keep the pH of the ion exchange liquid below a certain value.

[0043] (15) The present invention made to solve the above-mentioned problems is an ion exchange liquid used for ion exchange treatment of tempered glass containing an alkali metal component, wherein the ion exchange liquid contains a molten salt and a pH adjuster, and the pH adjuster is a boron compound.

[0044] When the ion exchange treatment of the tempered glass is performed using such an ion exchange liquid, the same effects as those of the above-mentioned corresponding configuration can be obtained.

[0045] Effects of the Invention

[0046] According to the present invention, it is possible to produce tempered glass having few surface defects and high surface strength while reliably suppressing an increase in the pH of an ion exchange solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram showing a manufacturing apparatus for tempered glass according to a first embodiment of the present invention.

[0048] Figure 2 This is a flowchart of the method for producing tempered glass according to the first embodiment of the present invention.

[0049] Figure 3 It is a schematic diagram showing a modification of the manufacturing apparatus of the tempered glass according to the first embodiment of the present invention.

[0050] Figure 4 It is a perspective view showing the test method of the ball-on-ring test.

[0051] Figure 5 This is a graph showing the accompanying KOH and B(OH) in Example 4 of the present invention. 3 Graph showing the change in pH with the addition of .

[0052] Figure 6 This is a diagram showing the relationship between the BOR intensity and the surface roughness Sa in Example 4 of the present invention.

[0053] Figure 7 This is a diagram showing an X-ray diffraction pattern in Example 5 of the present invention. DETAILED DESCRIPTION

[0054] Hereinafter, a manufacturing device for tempered glass, a manufacturing method for tempered glass, and an ion exchange liquid according to an embodiment of the present invention will be described. In addition, in each embodiment, the same symbols are added to corresponding components, so that repeated descriptions may be omitted. In each embodiment, when only a part of the structure is described, the structure of other embodiments previously described can be applied to the other parts of the structure. In addition, not only the structures explicitly described in the description of each embodiment can be combined, but in particular, as long as there is no obstacle in the combination, even if it is not explicitly stated, the structures of multiple embodiments can be partially combined with each other.

[0055] <First embodiment>

[0056] (Equipment for manufacturing tempered glass and ion exchange fluid)

[0057] like Figure 1As shown, the manufacturing apparatus of the tempered glass of the first embodiment is a processing apparatus for obtaining tempered glass by performing ion exchange treatment on tempered glass 1. The apparatus comprises: an ion exchange tank 3 storing ion exchange liquid 2; and a jig 4 holding tempered glass 1.

[0058] The ion exchange liquid 2 is a treatment agent that performs ion exchange with components in the tempered glass 1 by contacting the tempered glass 1. The ion exchange liquid 2 contains a molten salt 2a and a boron compound 2b. In the present embodiment, the boron compound 2b is contained in a container 5 that is permeable to the ion exchange liquid 2.

[0059] The molten salt 2a is a salt containing a component that can exchange ions with the component in the tempered glass 1, and is typically an alkali metal nitrate. The alkali metal nitrate preferably contains NaNO 3 、KNO 3 and LiNO 3 The composition of the molten salt 2a can be appropriately changed depending on the glass composition of the tempering glass 1, the conditions of the ion exchange treatment (for example, the treatment temperature and the treatment time), and the like.

[0060] In this embodiment, LiNO is used as the molten salt 2a. 3 and NaNO 3 A case where a mixed salt of 200 μm and 200 μm is used to perform a single-stage ion exchange treatment on the same tempering glass 1 will be described. In addition, the ion exchange treatment may be performed on the same tempering glass 1 in two or more stages.

[0061] LiNO 3 and NaNO 3 The mixing ratio of LiNO can be determined arbitrarily. 3 and NaNO 3 The mixing ratio of NaNO can be, in mass %, 3 30~100%, LiNO 3 0~70, preferably NaNO 3 70~100%, LiNO 3 0-30%, preferably NaNO 3 95-100%, LiNO 3 0~5%.

[0062] The boron compound 2b is a non-glass pH adjuster for lowering the pH of the ion exchange liquid 2, that is, the molten salt 2a. The boron compound 2b has high solubility in water. In this embodiment, the boron compound 2b contains B 2 O 3 and B(OH) 3Here, the so-called main component means that its content is 90 mass % or more, preferably 95 mass % or more, and more preferably 98 mass % or more relative to the total components constituting the boron compound 2b. In addition, the boron compound 2b may contain impurities (for example, 3 mass % or less).

[0063] Here, if the ion exchange liquid 2 is used for a long time at a high temperature, the pH may rise. This is because the OH in the ion exchange liquid 2 is decomposed due to the decomposition reaction of the molten salt 2a contained in the ion exchange liquid 2. - When the pH of the ion exchange liquid 2 (molten salt 2a) rises in this way, the OH in the ion exchange liquid 2 - This causes the glass surface to become rough, and the surface strength of the tempered glass may be reduced.

[0064] The decomposition reaction of molten salt 2a is easy to occur in LiNO 3 and NaNO 3 It is difficult to occur in KNO 3 This is because the temperature at which the decomposition reaction of the molten salt 2a occurs is determined by the LiNO 3 、NaNO 3 、KNO 3 Therefore, the boron compound 2b has a pH-lowering effect on the ion exchange liquid 2, and the molten salt 2a contains LiNO 3 and / or NaNO 3 , and, substantially does not contain KNO 3 Also, the so-called "substantially no KNO 3 ", meaning that KNO is not intentionally added to the molten salt 2a. 3 , the molten salt 2a is allowed to contain KNO dissolved from the tempering glass 1 3 Specifically, the so-called "substantially free of KNO 3 ”, which means that KNO in molten salt 2a 3 The content is 1 mass % or less.

[0065] The following shows LiNO 3 and NaNO 3 In the following reaction formula, H 2 O is considered to be atmospheric moisture dissolved in the ion exchange fluid.

[0066]

Chemical formula 1

[0067] RNO 3 +H 2 O→ROH+OH - +NO 2 ↑

[0068] wherein R is Na or Li.

[0069] The mechanism of pH increase is not limited to this, and may be explained by other mechanisms.

[0070] On the other hand, when the boron compound 2b is added to the ion exchange solution 2, the pH of the ion exchange solution 2 decreases. The mechanism of this is not clear, but as an example, it can be estimated as follows. + Or Na + , and H contained in boron compound 2b + Ion exchange is performed, and H released into the ion exchange solution 2 + Neutralizes OH in ion exchange solution 2 - It is considered that the pH of the ion exchange liquid 2 is lowered by such a neutralization reaction (dehydration reaction).

[0071] As a specific example, the following shows that B(OH) 3 An example of the reaction formula when added to the ion exchange solution 2.

[0072]

Chemical formula 2

[0073] 4B(OH) 3 +2ROH→R 2 B 4 O 7 +7H 2 O

[0074] wherein R is Na or Li.

[0075] Here, in the above-mentioned neutralization reaction process, the excess Li ions and Na ions in the ion exchange liquid 2 also serve as the source of B(OH) 3 The reaction product is adsorbed. In addition, it is believed that B 2 O 3 It also partially reacts with moisture in the air and may contain H + Therefore, even if B 2 O 3 The same neutralization reaction also occurs when it is added to the ion exchange liquid 2. The principle of pH reduction of the ion exchange liquid 2 is not limited to this, and may be explained by other principles.

[0076] The boron compound 2b is preferably added to the ion exchange solution 2 so that the pH of the ion exchange solution 2 becomes 8 or less. In this way, the surface strength of the tempered glass is improved. The threshold value of the pH of the ion exchange solution 2 is preferably 8 or less, and is 6 to 8.

[0077] In this specification, the term "pH of the ion exchange liquid 2" means the pH when the ion exchange liquid 2 is mixed with water to form an aqueous solution with a concentration of 20 mass %. The aqueous solution is prepared by cooling and solidifying the ion exchange liquid 2, pulverizing it, and dissolving it in water. The measurement temperature (liquid temperature) of the pH of the ion exchange liquid 2 is, for example, 25°C ± 5°C. The pH of the ion exchange liquid 2 is measured by, for example, a tabletop pH meter "F-71" manufactured by Horiba, Ltd.

[0078] The boron compound 2b is preferably added to the ion exchange liquid 2 so that the surface roughness Sa of the tempered glass is 3.0 nm or less. In this way, the surface strength of the tempered glass is improved. The threshold value of the surface roughness Sa of the tempered glass is preferably 3.0 nm or less, 1.5 nm or less, 1.0 nm or less, and 1.0 to 0.2 nm.

[0079] The boron compound 2b is preferably added to the ion exchange liquid 2 so that the BOR strength of the tempered glass becomes 1000 MPa or more. The threshold value of the BOR strength of the tempered glass is preferably 1000 MPa or more, 1200 MPa or more, or 1300 MPa or more.

[0080] The boron compound 2b is preferably added in a manner such that the content of the boron compound 2b is 0.1 to 10 parts by mass when the content of the molten salt 2a is 100 parts by mass. The content of the boron compound 2b is more preferably 0.1 to 10 parts by mass, 0.1 to 7 parts by mass, 0.1 to 5 parts by mass. If the content of the boron compound 2b is too little, a sufficient reduction in the pH of the ion exchange liquid 2 may not be obtained. On the other hand, if the content of the boron compound 2b is too much, the burden of equipment and the burden of removing the product from the boron compound 2b may increase. From the same point of view, the amount of the boron compound 2b added at one time is preferably 1% by mass or less.

[0081] The boron compound 2b is preferably added to the ion exchange liquid 2 in the form of a powder or an agglomerate of the powder. The agglomerate includes a pressed powder (e.g., a tablet). In the present embodiment, the boron compound 2b is added in the form of an agglomerate. If it is in the form of an agglomerate, the boron compound 2b gradually dissolves in the ion exchange liquid 2. Therefore, the duration of the pH lowering effect of the ion exchange liquid 2 generated by the boron compound 2b becomes longer, and the frequency of the addition treatment of the boron compound 2b can be reduced.

[0082] The ion exchange tank 3 is a tank for storing the ion exchange liquid 2. At least a portion of the contact surface of the ion exchange tank 3 with the ion exchange liquid 2 is made of a metal having corrosion resistance to the molten salt 2a. In the present embodiment, the inner surface of the ion exchange tank 3 is made of stainless steel. In addition, the ion exchange tank 3 preferably further includes: a fixture 4 for holding the tempering glass 1; an opening for entering and exiting the container 5 containing the boron compound 2b; and a cover (not shown) covering the opening.

[0083] The jig 4 is a member for holding the tempered glass 1. During the ion exchange treatment, the jig 4 is immersed in the ion exchange liquid 2 in the ion exchange tank 3 while holding the tempered glass 1. At least a portion of the contact surface of the jig 4 with the ion exchange liquid 2 is made of metal. In the present embodiment, the jig 4 is entirely made of stainless steel. The jig 4 is carried in and out of the ion exchange tank 3 by a transport device (not shown).

[0084] The container 5 is a separation member for separating the boron compound 2b from the tempering glass 1. The container 5 is immersed in the ion exchange liquid 2 in the ion exchange tank 3 with the boron compound 2b contained therein. In the present embodiment, the boron compound 2b contained in the container 5 is arranged at the bottom portion in the ion exchange tank 3 where the ion exchange liquid 2 is stored. Here, the so-called "bottom portion" refers to, for example, a portion below the tempering glass 1 immersed in the ion exchange liquid 2.

[0085] The aggregate of the boron compound 2b has a low density and floats in the ion exchange liquid 2, but when contained in the container 5, it can sink to the bottom portion of the ion exchange tank 3. Therefore, it is easy to maintain the state in which the boron compound 2b is isolated from the strengthening glass 1. Therefore, it is possible to prevent the unreacted boron compound 2b from adhering to the strengthening glass 1 (or the strengthened glass) and the jig 4 and being carried out of the ion exchange tank 3.

[0086] In addition, the aggregates of the boron compound 2b gradually permeate the container 5 by dissolving into the ion exchange liquid 2. A portion of the boron compound 2b that permeates the container 5 is fully dispersed in the ion exchange liquid 2 while rising in the ion exchange liquid 2 by buoyancy. Therefore, the pH of the entire ion exchange liquid 2 can be efficiently lowered.

[0087] The container 5 is made of a net, a screen or a porous member to allow the ion exchange liquid 2 to pass through. In the present embodiment, the container 5 is entirely made of stainless steel. The container 5 is carried in and out of the ion exchange tank 3 by a transport device (not shown).

[0088] The tempered glass 1 is a glass article before ion exchange treatment as an object of ion exchange treatment. In the present embodiment, the tempered glass 1 is exemplified as a rectangular plate. The plate thickness of the tempered glass 1 is, for example, 2.0 mm or less, more preferably 1.0 mm or less, and further preferably 0.3 mm to 0.9 mm. The length of the tempered glass 1 is, for example, 5 mm to 5000 mm, 15 mm to 1000 mm, 30 mm to 500 mm, 50 mm to 300 mm, 70 mm to 200 mm, and the width of the tempered glass 1 is 1 mm to 4000 mm, 10 mm to 1000 mm, 30 mm to 500 mm, 40 mm to 300 mm, 50 mm to 150 mm.

[0089] The tempering glass 1 is preferably an alkali aluminosilicate glass. 2 O, but in this embodiment, the tempered glass 1 contains 1 mol % or more of Li 2 The case of O will be described. The tempered glass 1 has substantially the same glass composition as the tempered glass to be manufactured.

[0090] The alkali aluminosilicate glass preferably contains SiO 2 40~80%,Al 2 O 3 1~30%, B 2 O 3 0~10%,MgO 0~10%,Li 2 O 1~28%, Na 2 O 1~25%, K 2 O 0~10%, P 2 O 5 0~10%, ZrO 2 0 to 10%. In particular, the alkali metal oxide (alkali metal component) preferably has the following content range.

[0091] Li 2 O is an ion exchange component. Li 2 O is a component that reduces high temperature viscosity and improves meltability and formability. 2 O is a component that increases Young's modulus. On the other hand, Li 2 O is also a component that dissolves during ion exchange treatment and deteriorates the ion exchange solution. 2The preferred lower limit range of O, in mol %, is 1% or more, 1.5% or more, 2% or more, 3% or more, 4% or more, 5% or more, 5.5% or more, 6.5% or more, and especially 7% or more. The preferred upper limit range is 28% or less, 20% or less, 15% or less, 13% or less, 12% or less, 11% or less, 10% or less, and especially less than 9%.

[0092] Na 2 O is an ion exchange component. Na 2 O is a component that increases high temperature viscosity and improves meltability and formability. 2 O is a component that improves the resistance to devitrification, and in particular, is a component that suppresses the devitrification that occurs during the reaction with the alumina molded body refractory. 2 If the content of O is too low, the meltability will decrease, the thermal expansion coefficient will decrease excessively, or the ion exchange rate will tend to decrease. 2 The preferred lower limit of O, in terms of mole %, is 1% or more, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, and particularly 7.5% or more. 2 If the content of O is too high, the viscosity of the phase separation will be easily reduced. In addition, the acid resistance will be reduced, or the components of the glass composition will be unbalanced, which may reduce the resistance to devitrification. 2 The preferred upper limit range of O is 25% or less, 22% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, and particularly 9% or less.

[0093] K 2 O is a component that reduces high temperature viscosity and improves meltability and formability. It is also a component that improves devitrification resistance and Vickers hardness. However, if K 2 If the content of O is too high, the viscosity of the phase separation will be easily reduced. In addition, the acid resistance will be reduced, or the lack of components in the glass composition will tend to reduce the resistance to devitrification. 2 The preferred lower limit range of O, in terms of mol %, is 0% or more, 0.01% or more, 0.02% or more, 0.1% or more, 0.2% or more, 0.3% or more, and particularly 0.35% or more. 2 The preferred upper limit range of O is 10% or less, 5% or less, 3% or less, 2% or less, 1% or less, 0.8% or less, 0.7% or less, 0.6% or less, and particularly less than 0.5%.

[0094] The above-mentioned tempered glass 1 can be produced, for example, as follows.

[0095] First, glass raw materials prepared according to the above glass composition are put into a continuous melting furnace, heated and melted at 1500°C to 1600°C to form molten glass. Next, the molten glass formed in the melting furnace is clarified, supplied to a forming device, formed into a plate shape by an overflow down-draw method, and slowly cooled. Thus, the tempered glass 1 can be produced. In addition to the overflow down-draw method, various forming methods can be used. For example, forming methods such as the float method, the down-draw method (the flow hole down-draw method, the re-draw method, etc.), the flattening method, and the pressing method can be used.

[0096] The tempered glass 1 may be bent after or simultaneously with the forming. In addition, the tempered glass 1 may be cut, drilled, surface polished, chamfered, end polished, etched, or the like.

[0097] (Method for manufacturing tempered glass)

[0098] Next, a method for producing tempered glass according to the first embodiment is described. In this method, the above-mentioned apparatus for producing tempered glass is used.

[0099] In this method, first, Figure 2 As shown in FIG. 1 , molten salt is prepared (step S1). Specifically, first, NaNO 3 and LiNO 3 The mixture is mixed and heated to melt to prepare a molten salt 2a.

[0100] Next, an ion exchange treatment is performed (step S2). Specifically, a plurality of sheets of strengthening glass 1 are held on a fixture 4 as a batch and immersed in an ion exchange solution 2 containing a molten salt 2a. The conditions such as the temperature of the ion exchange solution 2 and the immersion time in the ion exchange treatment can be determined arbitrarily, but the temperature of the ion exchange solution 2 is, for example, 350°C to 500°C, preferably 360°C to 470°C, 360°C to 450°C, 360°C to 430°C, and 360°C to 410°C. In addition, the immersion time is, for example, 0.1 to 30 hours, preferably 0.2 to 20 hours, 0.3 to 15 hours, 0.4 to 10 hours, and 0.5 to 5 hours. By performing an ion exchange treatment on the strengthening glass 1, a strengthened glass can be obtained.

[0101] After the ion exchange treatment of one batch is completed, the ion exchange treatment is performed on the next batch of tempered glass 1 , and the ion exchange treatment is repeatedly performed until the ion exchange of a predetermined number of batches is completed (No in step S3 ).

[0102] On the other hand, after the predetermined number of batches of ion exchange are completed (Yes in step S3 ), the pH of the ion exchange solution 2 is measured (step S4 ).

[0103] After the pH of the ion exchange liquid 2 is measured, it is determined whether the pH exceeds a predetermined threshold value (step S5). Specifically, in this embodiment, for example, it is determined whether the pH value of the ion exchange liquid 2 is higher than 8.

[0104] If the pH of the ion exchange liquid 2 is below a predetermined threshold value (eg, pH 8) (No in step S5 ), the next batch of ion exchange treatment is performed, and the above-mentioned processes from step S2 to step S5 are repeated.

[0105] On the other hand, if the pH of the ion exchange solution 2 exceeds a predetermined threshold value (eg, pH 8) (Yes in step S5 ), a process of adding a boron compound 2 b as a pH adjuster to the molten salt 2 a is performed (step S6 ).

[0106] In step S6, the container 5 containing the boron compound 2b is immersed in the ion exchange solution 2. The container 5 containing the boron compound 2b may be swung in the ion exchange solution 2. In this way, the diffusion rate of the boron compound 2b into the ion exchange solution 2 increases, and the rate at which the pH of the ion exchange solution 2 decreases can be accelerated.

[0107] After the addition process of step S6 is completed, the process of step S2 is performed on the next batch of tempered glass 1, and the above process is repeated. In addition, after the process of step S6, a waiting period of a predetermined time may be set until the pH adjustment of the ion exchange solution 2 by the boron compound 2b is completed to a certain extent, and then the process of step S2 is started. The waiting time from the process of step S6 to the start of step S2 can be arbitrarily determined, for example, more than 1 minute, more than 5 minutes, more than 10 minutes, more than 30 minutes, 1 hour to 24 hours, and 1 hour to 12 hours.

[0108] As described above, according to this method, even if the pH of the ion exchange solution 2 increases, the boron compound 2b can reliably reduce the pH of the ion exchange solution 2. This can suppress a decrease in the surface strength of the tempered glass produced by this method.

[0109] In addition, since the boron compound 2b has high solubility in water, even if the boron compound 2b adheres to the tempered glass, it can be easily removed by washing. In other words, the tempered glass produced by this method is unlikely to have surface defects caused by the boron compound 2b.

[0110] The tempered glass produced by the present method can be used, for example, as cover glass for smartphones, mobile phones, tablet computers, personal computers, digital cameras, touch screen displays, other display devices, vehicle-mounted display devices, vehicle-mounted panels, and the like.

[0111] <Second embodiment>

[0112] The tempered glass obtained in the first embodiment described above may be subjected to an additional ion exchange treatment. Figure 2 The ion exchange treatment (step S2 ) shown is the first stage ion exchange treatment, and a second stage ion exchange treatment (not shown) is further performed.

[0113] In the second stage ion exchange treatment, it is preferred to separately prepare and use a molten salt 2a (referred to as a first molten salt) having a higher KNO content than that used in the first stage ion exchange treatment. 3 A molten salt with a high mixing ratio (referred to as the second molten salt), preferably KNO 3 The mixing ratio is 90 mass % or more. According to such a treatment, a deep compressive stress layer can be formed in the first stage ion exchange treatment for the tempered glass, and a high surface compressive stress can be imparted in the second stage ion exchange treatment. In addition, in the second stage ion exchange treatment, it is preferred to adjust the composition of the molten salt, the treatment temperature, the treatment time, etc. in such a way that the surface compressive stress of the tempered glass reaches 700 MPa or more.

[0114] When the ion exchange treatment is performed in two stages in this manner, the boron compound 2b must be added to the ion exchange solution of the first stage, and can be optionally added to the ion exchange solution 2 of the second stage.

[0115] Furthermore, although the embodiments of the present invention have been described, the embodiments of the present invention are not limited thereto, and various modifications can be made without departing from the spirit of the present invention.

[0116] In the above embodiment, the pH of the ion exchange liquid 2 is measured, and the case where the addition treatment is determined based on the pH value is illustrated, but the above treatment can also be performed based on other characteristics. For example, in step S4, the surface roughness Sa of the tempered glass can be measured together with or instead of the pH measurement. Then, in step S5, it can be determined whether the surface roughness Sa of the tempered glass is lower than a predetermined threshold. In this case, the threshold of the surface roughness Sa of the tempered glass can be set to any value within a range of 3.0 nm or less, for example.

[0117] In the above embodiment, the pH measurement process is performed for each predetermined number of batches, but the pH measurement process may be performed for each ion exchange process performed on each batch of tempered glass 1. In this case, the determination process of step S3 may be omitted. With such a process, the addition process of step S6 can be performed at an appropriate timing, and the outflow of defective products can be more appropriately suppressed.

[0118] In the above-mentioned embodiment, the processing of steps S4 and S5 may be omitted. That is, the addition processing of step S6 may be performed when the ion exchange processing of the specified number of batches is completed (Yes in step S3). For example, when the increase in pH of the ion exchange liquid 2 can be predicted according to the number of batches, such processing can reduce the man-hours of steps S4 and S5 and improve production efficiency.

[0119] In the above-described embodiment, after the molten salt preparation step of step S1 and before the ion exchange treatment of step S2 , the addition treatment of step S6 may be performed to start production in a state where the boron compound 2b is previously added to the molten salt 2a.

[0120] In the above-mentioned embodiment, the addition treatment of step S6 can be performed during the ion exchange treatment of step S2. In other words, the boron compound 2b can be added in a state where the strengthening glass 1 is immersed in the ion exchange solution 2 in the ion exchange tank 3. However, from the viewpoint of suppressing the adhesion of the boron compound 2b to the strengthening glass 1, it is preferred to add the boron compound 2b in a state where the strengthening glass 1 is not immersed in the ion exchange solution 2 in the ion exchange tank 3.

[0121] In the above-mentioned embodiment, in step S6, the case where the boron compound 2b is contained in the container 5 and added to the ion exchange liquid 2 is described, but the method of adding the boron compound 2b is not limited thereto. Figure 3 As shown, the auxiliary tank 8 may be connected to the ion exchange tank 3 via the communication paths 6 and 7 through which the ion exchange liquid 2 can flow, the boron compound 2b may be added to the auxiliary tank 8, and the ion exchange liquid 2 to which the boron compound 2b is added in the auxiliary tank 8 may be supplied to the ion exchange tank 3. In this case, the auxiliary tank 8 functions as a separation member for separating the boron compound 2b from the tempered glass 1. In addition, the boron compound 2b may be directly added to the ion exchange liquid 2 stored in the ion exchange tank 3 or the auxiliary tank 8 instead of being contained in the container 5.

[0122] In the above-mentioned embodiment, the tempered glass may also be a crystallized glass. Crystallized glass is a glass in which inorganic crystals are precipitated by heat treatment (crystallization treatment) of amorphous glass, and the glass contains inorganic crystals. Here, the so-called amorphous glass refers to a glass in which no diffraction peak indicating a crystal is confirmed by powder X-ray diffraction. When the tempered glass is a crystallized glass, a heat treatment (crystallization) is further performed before the ion exchange treatment (step S2). In the heat treatment, for example, the tempering glass for the amorphous glass is heated at 700 to 840°C for 0.1 to 15 hours. Thus, as a precipitated crystal, at least one selected from β-eucryptite solid solution, β-spodumene solid solution and zirconium oxide is precipitated in the glass.

[0123] In the above embodiment, the tempered glass 1 and the tempered glass are rectangular plates, but are not limited to rectangular plates and can be applied to any shapes such as curved plates, disks, tubes, containers, and spheres.

[0124] Example 1

[0125] Hereinafter, the glass article of the present invention will be described based on examples. Note that the following examples are merely illustrative, and the present invention is not limited to the following examples at all.

[0126] Table 1 shows B(OH) 3 , B 2 O 3 and SiO 2 Solubility in water.

[0127]

Table 1

[0128]

[0129] As shown in Table 1, B(OH) 3 and B 2 O 3 The solubility is much higher than that of SiO 2 Therefore, if it is a boron compound, even if it adheres to the tempered glass, it can be easily removed by washing.

[0130] Example 2

[0131] Next, prepare NaNO as molten salt. 3 Single salt, NaNO 3 and LiNO 3 The ion exchange liquids composed of these molten salts were kept at high temperature for a long time to confirm whether the pH of the ion exchange liquid increased. The results are shown in Table 2.

[0132]

Table 2

[0133]

[0134] The pH in the table means the pH when the ion exchange liquid is mixed with water to form an aqueous solution with a concentration of 20 mass %. The above aqueous solution is prepared by cooling and solidifying the ion exchange liquid, pulverizing it, and dissolving it in water. The measurement temperature (liquid temperature) of the pH of the ion exchange liquid is 25°C ± 5°C. As a measuring device for the pH of the ion exchange liquid, a desktop pH meter "F-71" manufactured by Horiba, Ltd. is used.

[0135] It can be confirmed from Table 2 that if the ion exchange solution is kept at a high temperature for a long time, the pH of the ion exchange solution increases. 3 As the content increases, the pH of the ion exchange fluid rises faster.

[0136] Example 3

[0137] As the tempering glass, an alkali aluminosilicate glass having a plate thickness of 0.65 mm and a glass composition containing SiO in mol % was prepared. 2 60.5%, Al 2 O 3 18.8%, B 2 O 3 0.1%, K 2 O 0.4%, Na 2 O 8.1%, Li 2 O 7.2%, MgO 0.5%, P 2 O 5 4.3%, SnO 2 0.05% (converted in mass%, SiO 2 51.6%, Al 2 O 3 27.9%, B 2 O 3 0.3%, K 2 O 0.6%, Na 2 O 7.5%, Li 2 O 3.3%, MgO 0.3%, P 2 O 5 8.4%, SnO 2 0.1%).

[0138] By using NaNO 3 and LiNO 3 KOH was added to the molten salt to simulate the deterioration of the ion exchange liquid, so that the pH of the ion exchange liquid increased. 2 O 3 , try to lower the pH of the ion exchange liquid. Then, after the first stage of ion exchange treatment is performed on the tempered glass having the above-mentioned glass composition using the ion exchange liquid in which the pH is lowered, the second stage of ion exchange treatment is performed using an ion exchange liquid composed of a different molten salt. Then, the BOR strength (surface strength) and the like of the tempered glass obtained by performing the ion exchange treatment in these two stages are measured. The results are shown in Tables 3 and 4. In addition, the ion exchange liquid used in the first stage of the ion exchange treatment means that the usage period becomes longer as the number of days used in the table increases.

[0139]

Table 3

[0140]

[0141]

Table 4

[0142]

[0143] In the table, CS represents the compressive stress on the surface, DOC represents the depth of the compressive stress layer, DOL represents the diffusion depth of potassium ions, CT represents the tensile stress at the center of the plate thickness, BOR strength represents the surface strength in a ball-on-ring test, and white turbidity represents a poor appearance that looks white and turbid.

[0144] CS, DOC, DOL, and CT can be derived based on values ​​measured using a surface stress meter (e.g., FSM-6000LE manufactured by Orihara Corporation) or values ​​synthesized from values ​​measured using a surface stress meter and a scattered light photoelastic stress meter (e.g., SLP-1000 manufactured by Orihara Corporation), for example.

[0145] BOR strength through Figure 4 The ball-on-ring test is shown in the figure. Specifically, the test sample (tempered glass) 9 is placed on a ring fixture 10 with an inner diameter of 25 mm, and the tip ball fixture 11 with a diameter of 12.5 mm is brought into contact with the test sample 9. The tip ball fixture 11 is lowered toward the center of the ring fixture 10 at a speed of 0.5 mm / min to apply a load. The breaking load (unit: MPa) when the test sample 9 is broken is taken as the BOR strength. The BOR strength is the average value of 9 measurements.

[0146] The white turbidity is determined by visually measuring the appearance of the sample (tempered glass) and judging whether white turbidity is observed as an appearance defect.

[0147] As shown in Tables 3 and 4, by adding B 2 O 3 , the pH of the ion exchange solution can be lowered (samples No. 4-3, 4-4, 5-3, and 5-4). In addition, after the ion exchange solution deteriorates, the BOR strength of the tempered glass decreases. However, if the pH of the ion exchange solution is lowered by B 2 O 3 By adding , the BOR strength of the tempered glass was restored to below 8 (sample No. 4-4, 5-4).

[0148] Example 4

[0149] As the tempering glass, an alkali aluminosilicate glass was prepared. The plate thickness was 0.70 mm. As the glass composition, SiO2 59.5%, Al 2 O 3 19.0%, B 2 O 3 0.3%, K 2 O 0.4%, Na 2 O 8.4%, Li 2 O 7.7%, MgO 0.5%, P 2 O 5 4.1%, SnO 2 0.1% (converted by mass%, SiO 2 51.6%, Al 2 O 3 27.9%, B 2 O 3 0.3%, K 2 O 0.6%, Na 2 O 7.5%, Li 2 O 3.3%, MgO 0.3%, P 2 O 5 8.4%, SnO 2 0.1%).

[0150] By using NaNO 3 and LiNO 3 KOH was added to the molten salt to simulate the deterioration of the ion exchange liquid. Then, B(OH) 3 , try to lower the pH of the ion exchange solution. In order to simulate the continuous deterioration of the ion exchange solution, KOH and B(OH) 3 The results are shown in Figure 5 middle.

[0151] like Figure 5 As shown, by adding B(OH) 3 , which can continuously lower the pH of the ion exchange liquid.

[0152] Alternatively, add B(OH) using 3 , the ion exchange liquid with a lowered pH was tried, and after the first stage of ion exchange treatment was performed on the tempered glass having the above glass composition, the second stage of ion exchange treatment was performed using an ion exchange liquid composed of a different molten salt. Then, the surface roughness Sa and BOR strength (surface strength) of the tempered glass obtained by performing the ion exchange treatment in these two stages were measured. The results are shown in Table 5. In addition, the relationship between the measured surface roughness Sa and BOR strength is shown in Figure 6In addition, the ion exchange liquid used in the first stage ion exchange treatment means that the usage period becomes longer as the number of used days in the table increases.

[0153]

Table 5

[0154]

[0155] The surface roughness Sa is a value measured using a white light interferometer VertScan manufactured by Ryoka System Co., Ltd. The surface roughness Sa is an average value of three measurements.

[0156] As shown in Table 5, the sample No. 6-1, which used the ion exchange solution before deterioration in the first stage of ion exchange treatment, had a BOR strength of 1517 MPa (referred to as the standard BOR strength). In contrast, the samples in which the deteriorated ion exchange solution with a pH higher than 8 was used in the first stage of ion exchange treatment had a BOR strength that was about 10 to 25% lower than the above standard BOR strength (for example, samples No. 6-12 and 6-15). On the other hand, the samples using the addition of B(OH) 3 In contrast, for the samples of the ion exchange solution whose pH was restored to 8 or less in the first stage of ion exchange treatment, the reduction in BOR intensity was restored to within 3% of the standard BOR intensity at most (for example, sample No. 6-22).

[0157] according to Figure 6 , it can be confirmed that the BOR strength is negatively correlated with the surface roughness Sa. In addition, it can be seen that in samples No. 6-1 to 6-23, although the glass surface did not become turbid, the deterioration of the surface roughness such as the absence of turbidity would also strongly affect the BOR strength. Moreover, in all samples in which the ion exchange solution with a pH higher than 8 was used in the first stage of ion exchange treatment, the surface roughness Sa was higher than 1.0. Therefore, it can be said that the ion exchange solution used in the first stage of ion exchange treatment (containing LiNO 3 and / or NaNO 3 , and, substantially does not contain KNO 3 The pH of the molten salt) is preferably adjusted to 8 or less by adding a boron compound.

[0158] Example 5

[0159] When a boron compound is added to an ion exchange solution containing Li ions, it is confirmed whether the boron compound actually adsorbs Li ions. Specifically, the additive precipitated at the bottom of the ion exchange solution tank of Sample No. 6-23 of Example 4 is scooped out and recovered, and the recovered additive is dried and the surface X-ray diffraction (XRD) pattern is measured.

[0160] The ion exchange solution of sample No. 6-23 was used for the 23rd day, and B(OH) was first added as a boron compound. 3 After that the ion exchange solution was added on the 17th day.

[0161] The measurement conditions of the X-ray diffraction pattern are as follows.

[0162] (1) Measurement device: Aeris manufactured by Spectris Corporation

[0163] (2) Light source: Cu tube ball (wavelength λ: 1.54Å)

[0164] (3) Measurement range (2θ): 5 to 60°

[0165] (4) Step size: 0.01°

[0166] The X-ray diffraction pattern is shown in Figure 7 As shown in the figure, there are no peaks from boric acid and boron oxide in the X-ray diffraction spectrum, and only peaks from lithium borate or sodium borate are confirmed. This confirms that even a small amount of 5 mass % LiNO 3 The Li ions contained in the boron compound can also be reliably used as B(OH) 3 adsorption. In addition, the X-ray diffraction pattern also includes NaNO 3 This is because the components of the ion exchange liquid contained as contaminants in the additive to be measured were measured.

[0167] Description of Reference Numerals

[0168] 1 Strengthening glass

[0169] 2 Ion exchange fluid

[0170] 2a Molten salt

[0171] 2b Boron compounds

[0172] 3 Ion exchange tank

[0173] 4. Fixture

[0174] 5. Container

[0175] 6, 7 Connecting Paths

[0176] 8 Auxiliary slots

[0177] 9. Measuring samples

[0178] 10 Ring clamp

[0179] 11 Front ball clamp

Claims

1. A method for manufacturing tempered glass, characterized in that: The method comprises the step of bringing an ion exchange liquid into contact with a tempered glass containing an alkali metal component to perform an ion exchange treatment on the tempered glass, wherein: The ion exchange liquid comprises a molten salt and a pH adjuster, The pH adjuster is a boron compound.

2. The method for producing tempered glass according to claim 1, wherein: The pH adjuster contains at least one of B2O3 and B(OH)3 as the boron compound.

3. The method for producing tempered glass according to claim 1 or 2, wherein: In the ion exchange liquid, the content of the pH adjuster is 0.1 parts by mass to 10 parts by mass, based on 100 parts by mass of the molten salt.

4. The method for producing tempered glass according to claim 1 or 2, wherein: The pH of the ion exchange liquid when mixed with water to prepare an aqueous solution with a concentration of 20 mass % is 8 or less.

5. The method for producing tempered glass according to claim 1 or 2, wherein: The content of the pH adjuster in the ion exchange solution is adjusted so that the surface roughness Sa of the tempered glass is 3.0 nm or less.

6. The method for producing tempered glass according to claim 1 or 2, wherein: The pH adjuster is contained in the ion exchange liquid in the form of powder or powder aggregate.

7. The method for producing tempered glass according to claim 6, wherein: The ion exchange treatment is performed by placing the ion exchange solution and the tempering glass in an ion exchange tank, The pH adjuster is disposed in the ion exchange tank in a state of being isolated from the strengthening glass by a partition member that allows the ion exchange liquid to permeate.

8. The method for producing tempered glass according to claim 7, wherein: The pH adjuster is disposed at a bottom portion of the ion exchange tank using the partition member.

9. The method for producing tempered glass according to claim 1 or 2, wherein: The molten salt contains at least one of LiNO 3 and NaNO 3 .

10. The method for producing tempered glass according to claim 9, wherein: The molten salt contains substantially no KNO 3 .

11. The method for producing tempered glass according to claim 9, wherein: The method comprises the step of performing a two-stage ion exchange treatment, wherein the ion exchange solution is used in the first stage ion exchange treatment.

12. The method for producing tempered glass according to claim 1 or 2, wherein: The tempering glass is an alkali aluminosilicate glass containing 1 mol % or more of Li2O as a glass composition.

13. The method for producing tempered glass according to claim 12, wherein: The tempering glass contains, in mol%, SiO2 40% to 80%, Al2O3 1% to 30%, B2O3 0% to 10%, MgO 0% to 10%, Li2O 1% to 28%, Na2O 1% to 25%, K2O 0% to 10%, P2O5 0% to 10%, and ZrO2 0% to 10% as a glass composition.

14. The method for producing tempered glass according to claim 1 or 2, wherein: It also has the following processes: a step of measuring the pH of the ion exchange liquid; and, A step of adding the pH adjuster to the ion exchange liquid based on the pH measurement result.

15. An ion exchange liquid, characterized in that: An ion exchange liquid for ion exchange treatment of tempered glass containing an alkali metal component, wherein: Contains molten salt and pH adjuster, The pH adjuster is a boron compound.

Citation Information

Patent Citations

  • Method for producing chemically strengthened glass

    JP2021059481A

  • Reinforced glass, and method for producing reinforced glass

    WO2020075709A1